PENGARUH ELECTRONIC WORD OF MOUTH MEDIA SOSIAL INSTAGRAM DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN KOPI JANJI JIWA DI KARAWANG - Rahma Suryani; Dede Jajang Suyaman (Jurnal Apresiasi Ekonomi, 2022)
The purpose of this study is to find out and analyze the factors that affect consumers in making purchasing decisions. Independent variables consist of Electronic Word of Mouth (EWOM) on Instagram social media (X1) and Brand Image (X2). A dependent variable is the decision to purchase soul appointment coffee in Karawang . By using an unlimited population so that it gets a total of 349 respondents, using the sample method that is Accidental Sampling. The analysis used is path analysis resulting from Y = 0.768 X1 + 0.139 X2 + Ɛ. Based on Test F and Test t results obtained that variable Electronic Word of Mouth (EWOM) on social media and Brand Image have a positive and significant effect on purchasing decisions. In this study obtained a determination coefficient value (R2) of 0.720 meaning a good determination coefficient model. This indicates that consumer purchasing decisions towards purchasing decisions of Kopi Janji Jiwa consumers in Karawang are influenced by variations of both variable independent, electronic word of mouth (EWOM) on social media and Brand Image. While the remaining 28% is influenced by other variables that are not studied.